PENGARUH MOTIVASI KERJA,RELIGIUSITAS,KEPUASAN KERJA,DISIPLIN KERJA,DAN SISTEM PENGENDALIAN AKUNTANSI TERHADAP KINERJA KARYAWAN (Studi Empiris Pada Baitul Maal Wat Tamwil di DIY) - Nisa Fajri (FE UMY, 2015)
This study at analyzing and providing emperical evidences of the influence of work motivation, religiosity,job satisfaction ,work dicipline, and accounting control system on employees perfomance. This analysis applies the independet variabels such as work motivation,religiosity,job satisfaction,work dicipline,and accounting control system. Meanwhile, the dependent variabel is the perfomance of employees. The sample used in this study are employees who work in the accounting Baitul maal wa tamwil in Yogyakarta. Samples are taken by distributing questionnaires to the concerned respondents. The samples consist of 65 samples. The statistical methods employ SPSS, with statistical hypotesis testing on the value of the test statistic. The result of the analyisis by employing all the independent variabel indicate that work motivation,religiosity,and accounting control system has no effect on employees. Job satisfaction and work dicipline has a positive effect on the employees